2023
DOI: 10.1002/pc.27422
|View full text |Cite
|
Sign up to set email alerts
|

Study on durability of transverse shear properties for novel carbon/glass hybrid fiber‐reinforced polymer bars in simulated concrete environments

Abstract: Durability on the transverse shear properties of hybrid fiber-reinforced polymer (HFRP) bar may control the cross-sectional load-bearing capacity and failure mode of the HFRP bar reinforced concrete members due to its strength degradation with time. Herein, the degradation of novel carbon/glass (C/G)-HFRP bars were accelerated in simulated concrete environments at 60 C to investigate the effects of fiber volume fraction and distribution pattern, matrix resin volume fraction, exposure environment, and period on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The TSS retention of BFRP bars coated with SSGM‐4 after 240 days of immersion was 69.3%. Since the main factor affecting TSS is the resin matrix, 15,39 one possible reason for this trend is the more densified microstructure of SSGM, which postponed the penetration of water molecules and OH¯ ions and thus mitigated the hydrolysis of the resin matrix. These findings revealed that SSGM coating provides better protection for BFP bars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TSS retention of BFRP bars coated with SSGM‐4 after 240 days of immersion was 69.3%. Since the main factor affecting TSS is the resin matrix, 15,39 one possible reason for this trend is the more densified microstructure of SSGM, which postponed the penetration of water molecules and OH¯ ions and thus mitigated the hydrolysis of the resin matrix. These findings revealed that SSGM coating provides better protection for BFP bars.…”
Section: Resultsmentioning
confidence: 99%
“…The authors also suggested that future work needs to be conducted on the effect of prestress load 38 . These findings highlight the importance of considering shear behavior when evaluating prestressed BFRP bars, and indicate that variations in ILSS and TSS can serve as useful indicators of bar deterioration 39 . However, prior studies have not yet detected the long‐term shear behavior of BFRP bars coated with SSGM.…”
Section: Introductionmentioning
confidence: 98%
“…Fiber-reinforced polymer (FRP) composites are widely used in ship hull, airframe, automotive, and wind turbine structural applications due to their high specific strength and stiffness. [1][2][3][4][5][6][7][8][9][10] However, because of the low matrix toughness and the poor interfacial interaction between fiber and matrix, FRPs are more susceptible to defects and damages, leading to rapid growth cracks and the delamination behaviors and shortening the service life of FRPs. [11][12][13] Therefore, improving the interlaminar shear strength (ILSS) of FRPs and healing the damage are key issues for enhancing the service life of composites.…”
Section: Introductionmentioning
confidence: 99%